2015
DOI: 10.3389/fpsyg.2015.00275
|View full text |Cite
|
Sign up to set email alerts
|

The neural substrates of response inhibition to negative information across explicit and implicit tasks in GAD patients: electrophysiological evidence from an ERP study

Abstract: Background: It has been established that the inability to inhibit a response to negative stimuli is the genesis of anxiety. However, the neural substrates of response inhibition to sad faces across explicit and implicit tasks in general anxiety disorder (GAD) patients remain unclear.Methods: Electrophysiological data were recorded when subjects performed two modified emotional go/no-go tasks in which neutral and sad faces were presented: one task was explicit (emotion categorization), and the other task was im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 85 publications
(107 reference statements)
2
7
0
Order By: Relevance
“…On the behavioral level, the observed pattern in the present study partly resembles findings in previous studies (24,25,31) such that MDD patients showed lower accuracy while GAD patients exhibited comparable accuracy with HC. However, while the previous studies reported emotion-specific inhibitory control deficits in MDD patients the present study found a general impairment in no-go accuracy irrespective of emotional context.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the behavioral level, the observed pattern in the present study partly resembles findings in previous studies (24,25,31) such that MDD patients showed lower accuracy while GAD patients exhibited comparable accuracy with HC. However, while the previous studies reported emotion-specific inhibitory control deficits in MDD patients the present study found a general impairment in no-go accuracy irrespective of emotional context.…”
Section: Discussionsupporting
confidence: 90%
“…In comparison, research on emotional-context dependent neurofunctional alterations in GAD is scarce. One study reported decreased right DLPFC amplitudes in GAD patients compared to healthy controls during inhibition of negative information in an explicit emotional inhibition paradigm, while the patients exhibited intact processing during an implicit emotional inhibition paradigm (31).…”
Section: Introductionmentioning
confidence: 99%
“…EPN waveform in panic disorder (PD) and healthy controls (HCs) occurring by different SFs and emotion at the averaged PO7 and PO8. evoked largely by facial emotional expressions, such as fear and threat rather than neutral expressions (Rossignol et al, 2005;Yu et al, 2015). However, there is inconsistent evidence regarding whether people with anxiety disorder show abnormal VPP compared to healthy subjects.…”
Section: Vertex Positive Potentialmentioning
confidence: 95%
“…However, there is inconsistent evidence regarding whether people with anxiety disorder show abnormal VPP compared to healthy subjects. Yu et al (2015) found that VPP amplitude was significantly increased, and latency was shorter in sad faces compared to neutral faces. In addition, VPP amplitude was larger as a trend level in patients with generalised anxiety disorder compared to HCs (Yu et al, 2015).…”
Section: Vertex Positive Potentialmentioning
confidence: 96%
See 1 more Smart Citation